2021
DOI: 10.21037/atm-21-3181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MAP3K15 as a potential prognostic biomarker and correlation with immune infiltrates in osteosarcoma

Abstract: Background: Osteosarcoma (OS) is a type of primary malignant tumor, and increasing evidence shows the clinical benefits of immunotherapy in treating OS. However, the lack of comprehensive studies on the complex OS immune microenvironment hinders the application of immunotherapy. Thus, this study aimed to systematically explore the immune characteristics of OS and identify novel biomarkers for OS treatment.Methods: We systematically studied the immune score and proportions of infiltrating immune cells in OS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies have found that members of the MAPK family function in a protein kinase signaling cascade and that MAP3K proteins play a role in regulating apoptosis [ 22 ]. It was found that MAP3K15 may be involved in tumorigenesis and development [ 23 ]. Importantly, our study identified mutations of the MAP3K15 gene in the dPGCMN tissue of patient 2#, which may have impaired the normal apoptotic program of melanocytes leading to uncontrolled cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that members of the MAPK family function in a protein kinase signaling cascade and that MAP3K proteins play a role in regulating apoptosis [ 22 ]. It was found that MAP3K15 may be involved in tumorigenesis and development [ 23 ]. Importantly, our study identified mutations of the MAP3K15 gene in the dPGCMN tissue of patient 2#, which may have impaired the normal apoptotic program of melanocytes leading to uncontrolled cell proliferation.…”
Section: Discussionmentioning
confidence: 99%